2021
DOI: 10.1016/j.coviro.2021.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-electron microscopy of nodavirus RNA replication organelles illuminates positive-strand RNA virus genome replication

Abstract: The nodavirus flock house virus recently provided a well-characterized model for the first cryo-electron microscope tomography of membrane-bound, positive-strand RNA ((+)RNA) virus genome replication complexes (RCs). The resulting first views of RC organization and complementary biochemical results showed that the viral RNA replication vesicle is tightly packed with the dsRNA genomic RNA replication intermediate, and that (+)ssRNA replication products are released through the vesicle neck to the cytosol throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…flaviviruses and nodaviruses. Whereas nothing is yet known about any flavivirus neck complex, cryo-electron tomography has revealed that nodaviruses have a neck complex of similar dimensions, albeit different architecture, than the alphavirus neck complex we present here (34,35). Strikingly, even the double-membrane vesicles-type replication organelle of coronaviruses has a protein complex at the neck connecting its lumen with the cytosol (36).…”
Section: Discussionmentioning
confidence: 66%
“…flaviviruses and nodaviruses. Whereas nothing is yet known about any flavivirus neck complex, cryo-electron tomography has revealed that nodaviruses have a neck complex of similar dimensions, albeit different architecture, than the alphavirus neck complex we present here (34,35). Strikingly, even the double-membrane vesicles-type replication organelle of coronaviruses has a protein complex at the neck connecting its lumen with the cytosol (36).…”
Section: Discussionmentioning
confidence: 66%
“…Alphaviruses replicate their genomes in membrane-derived ultrastructures termed spherules that contains the negative-strand (-) RNA template likely in form of dsRNA intermediate species, and the RC assembled from nsPs (1, 2). The RC likely creates a favorable compartment for RNA synthesis that minimizes the host immune response to dsRNA intermediates and possesses multifunctional enzymes capable of orchestrating rapid and efficient synthesis of viral genomic and subgenomic RNAs (3)(4)(5)(6)(7)(8). nsP1-4 are known to localize to the RCs and are essential to viral RNA replication through their own distinct enzymatic and non-enzymatic functions: nsP1 displays methyl-and guanylyltransferase activities required for viral RNA 5' cap synthesis and plasma membrane anchoring ability; nsP2 consists of an N-terminal superfamily 1 RNA helicase and a cysteine protease at the C-terminal region responsible for polyprotein autoprocessing; nsP3 contains an ADP-ribosyl binding and hydrolase domain and a disordered region as the host factor interaction hub; lastly, nsP4 is the RNA-dependent RNA polymerase (RdRp) for viral RNA synthesis.…”
Section: Main Textmentioning
confidence: 99%
“…The ultrastructure of the distantly related nodavirus Flock House virus (FHV) RC provided the first structural insight for RC assembly in the form of a dodecameric crown-shape scaffold (7). Similarly, multimeric ring-shaped ultrastructures were recently reported in both coronavirus RC (8) and alphavirus nsP1 (9,10). However, these ultrastrectures have yet to explain the organization of multi-component RCs and the molecular mechanism by which RCs ultimately achieve RNA synthesis and transport to the cytosol.…”
Section: Main Textmentioning
confidence: 99%
“…The processes of positive-strand RNA virus genome replication and transcription occur within the cytosol of infected cells, in association with membrane-bound replication organelles (ROs), which have two general morphologies ( Nguyen-Dinh and Herker, 2021 ; Unchwaniwala et al, 2021 ; Wolff and Barcena, 2021 ). Some viruses, such as flaviviruses and nodaviruses, form “spherule”-like ROs, sac-like invaginations into larger membranes that feature a neck, such that the RNA-containing spherule interior is contiguous with the cytosol.…”
Section: General Principles Of Positive-strand Rna Virus Replicationmentioning
confidence: 99%